Maluku Leading Sector Determination Overlay Model - Jefri Tipka (Department of Mathematics, Faculty of Mathematics and Natural Sciences, Pattimura University, Ambon, Indonesia, 2021)
The Overlay Model is an analysis in economic development planning used to understand economic development, the Overlay Model is a combination modeling of LQ (Location Quentient), MRP (Growth Ratio Model) and modified SS-EM (Shift Share Estaban Marquillas). This study aims to analyze the leading sectors in Maluku Province and their effects among external and internal areas. The results show that the economic development in Maluku Province during the 2010-2020 period have three leading sectors that are potential in palying the economy. The results of the research can be used as a policy evaluation for the local government and a consideration in future decision making.